Стан і перспективи дослідження та інтродукції в Україну видів родини Papaveraceae - Klimenko, G.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
This article deals with species of Papaveraceae family the degree of their research and analysis conducted concerning their agricultural value. The state of introduction in Ukraine and other countries of the world has been considered here. The ways of introduction for increasing the assortment of decorative plants in Ukraine are outlined.